Tests for building model characteristics of physical fitness of athletes aged 16-17 in mas-wrestling - Cherkashin I.A. ,; Kaman Lui,; Kudrin E.P. ,; Cherkashina E.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to selection of essential tests for assessing the physical fitness of young athletes in the sport of mas-wrestling. Methods and structure of the study. General and special physical fitness was tested for 53 athletes specializing in mas-wrestling, whose age was 16,28± 0,68 years, representatives of weight categories up to 50 kg (15 people), up to 60 kg (13 people), up to 70 kg (25 people). To build model characteristics of physical fitness, a set of pedagogical methods was used. tests and dynamometry to determine the strength of the hand and fingers. The indicators of the athletes' special physical fitness were determined using a modified «Lower Thrust» simulator. A paired correlation analysis was carried out using the licensed IBM SPSS Statistics 22.0 program. The research was conducted on the basis of the V. Manchaara Republican Center for National Sports and the Children's and Youth Sports School № 1. Yakutsk. Results and conclusions. Closely interrelated indicators of general and special physical fitness were determined based on correlation analysis, where correlation coefficients ranged from r=0,701 to r=0,977, which allowed us to select significant tests for constructing model characteristics of athletes. The complex includes: running 60 m, running 1000 m, long jump from a place, long jump from a place with your back in the direction of movement, hanging on a high crossbar, bending and unbending your arms while lying down, squatting with a barbell, pulling up from hanging on a high crossbar, leaning forward from a sitting position, as well as wrist and finger dynamometry.